Fluid Resuscitation and Initial Management in Patients Presenting with Sepsis in the General Ward - Sung Won Chang; Juwhan Choi; Jee Youn Oh; Young Seok Lee; Kyung Hoon Min; Gyu Young Hur; Sung Yong Lee; Jae Jeong Shim; Jae Kyeom Sim (Life)
The optimal management of hospital-presenting sepsis remains poorly understood. We investigated the initial management in patients presenting with sepsis in the general ward, the association between fluid resuscitation and clinical outcomes, and the factors affecting fluid resuscitation. A retrospective study was conducted on patients who presented with sepsis-induced hypotension in the general ward. Patients were divided into Less 30 (fluid resuscitation less than 30 mL/kg) and More 30 (fluid resuscitation 30 mL/kg or more) groups. Multivariable logistic regression analysis was performed. The median resuscitation fluid volume was 500 mL (9.2 mL/kg) and 2000 mL (35.9 mL/kg) in the Less 30 (n = 79) and More 30 (n = 11) groups, respectively. The intensive care unit (ICU) mortality was similar between the two groups (43.0% vs. 45.5%). Twenty-two patients received continuous renal replacement therapy (CRRT) in the Less 30 group, whereas none received it in the More 30 group (27.8% vs. 0%). Fluid resuscitation ≥30 mL/kg was not associated with ICU mortality. Low body weight and systolic blood pressure were associated with fluid resuscitation ≥30 mL/kg. Most hospital-presenting sepsis patients received less than 30 mL/kg of fluid, and fluid resuscitation was not associated with ICU mortality.